Peran Konseling Individu Dengan Teknik Stress Inoculation Training (SIT) Untuk Mengatasi Stress Pada Lansia - Yolanda Setio Rini; Suryati Suryati; Lena Marianti (Journal of Society Counseling, 2023)
This research is entitled "The Role of Individual Counseling Using Stress Inoculation Training (SIT) Techniques to Overcome Stress in the Elderly at PSLU Harapan Kita Palembang". The purpose of this stress inoculation training technique is to find out the description of stress in the elderly and the application of stress inoculation training techniques to deal with stress in the elderly. The method used in this research is a qualitative research method. The results of this study are that before carrying out individual counseling it can be seen that the elderly do not have sensitivity to the stress disorders they sometimes experience, which is marked by indicators that include references to determine the existence of stress disorders that are being experienced such as headaches, loss of appetite, difficulty sleeping, irritable, and likes to be alone. After providing individual counseling and techniques that the elderly can implement in their daily lives, the overcoming of elderly stress begins to be seen when the elderly can be consistent in applying the techniques provided as seen from the perspective of the elderly who remain calm, able to control their breath, think positively, and are able to process their emotions to avoid stress.